Nationalism in the Balkans A reality to be challenged by our Diplomacies - Mozali, Zemaida; Mozali, Fleino (ANGLISTICUM. Journal of the Association-Institute for English Language and American Studies, 2016)
The Balkans and nationalism are two terms already related in some natural way, because of their history and developments during the years, decades and centuries. Our paper aims to make an analysis of the region, which has been historically related to nationalism, a reality that characterizes the relations among our people. This topic has been the object of study for many scholars of political science or international relations as part of them. It might also be of interest to a wider audience, considering that nationalism is also related to culture and our everyday life. The deeper study and understanding of this concrete phenomenon can work very well too ―reconcile the clash of cultures in our region. The issue per se is very complex and, despite the fact that it was treated fairly, again it is intriguing because, in the course of the years, there have occurred many events in our small, but difficult region. These events will be part of this work, treated chronologically, or/and intertwined with the theoretical framework, also with the concept of nationalism, its interdependence with different countries, where the context gives it different colors. This fact makes it sometimes even more aggressive and with consequences, as it has happened many times in our region. What we see as important and which has been quite influential in developments in the region, relates to the Great Yugoslavia, which has generated often conflicts, and which was a certain "apple of quarrel", taking into account the minorities or ethnic differences. These developments came out highlighted along with its dissolution. Despite the road chosen by the Balkans, i.e., the Euro-Atlantic perspective, we think that such a topic is current again. Despite the efforts of Europe itself, as well as the efforts of ―would be European‖ countries, to create and cultivate a European identity, where borders do not need to be any more important, meaningless reason for conflicts or wars, still there is reason for concern on the issue, i.e., extreme nationalism in our region. Keywords: Nationalism, Balkans, conflicts, cultures, ethnic differences.